Hukum Merokok pada Keadaan Ihram Beserta Implikasinya Dalam Ibadah Haji dan Umrah - Sayyid Tashdyq; Muhammad Syahrir; Abdil Munzir (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
Among the bad habits that are often witnessed during the implementation of the Hajj and Umrah are smoking, the smoke is very disturbing comfort of the people around, especially done in the area of ​​al-Haram, masyarilharam even in ‘arafah. Though the Prophet Sallallaahu ‘Alaihi wa Sallam has given good news in the form of Paradise for those who hajj mabrur. Therefore, it is necessary to study the impact of smoking on the Hajj or Umrah. This research uses library research method by collecting references relating to the object of study, heuristic approach through personal experience, normative approach in breaking down the law of ihram in the Hajj and Umrah, and the methodology is descriptive analysis. The results of this study stated that smoking is haram, so that it includes violations in berihram which can have an impact on reducing the culprit's reward, and it is feared not to reach a hajj that is mabrur, or umrah that maqbulah on the side of Allah Subhanahu wa Ta'ala. Although it does not affect the validity of worship as long as the harmony and its requirements are met. For this reason, it is desirable for active smokers to abandon this bad habit, especially when carrying out the Hajj and Umrah, as well as the mentors to always remind their congregants not to commit these violations. We recommend reprimanding and advising them when found violating these directives to stop in order to get the virtue of this noble worship with the permission of Allah Subhanahu wa Ta'ala.